Greening the East African Drylands: Agroforestry for Climate Resilience and Food Security - Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
East Africa’s dryland regions face escalating challenges from climate change, food insecurity, and weak natural resource governance (IGAD, 2020, pp. 37–39). Increasingly frequent droughts, accelerated land degradation, and declining water availability are intensifying competition over natural resources (World Bank, 2022, p. 15). These tensions have triggered conflicts between farmers and pastoralists (UNEP, 2021, Ch. 4), heightened human-wildlife interactions (WWF, 2023), and led to displacement linked to conservation efforts—factors that collectively threaten human security across the region (Ackerl et al., 2023; African Union, 2021). This crisis is underpinned by three interlinked drivers. •Environmental degradation, including desertification (IPCC, 2019), erratic rainfall patterns (ICRAF, 2022), and a decline in soil fertility; •Socioeconomic inequities, such as widespread poverty (World Bank, 2023), population pressures, and unequal access to land, especially for women (AU & UN Women, 2021); •Institutional and policy gaps, including weak governance systems (IGAD, 2021) and insufficient investment in sustainable land management (AfDB, 2022). If these trends persist without targeted interventions, they will further undermine livelihoods and regional stability. Agroforestry—integrating trees into farmland—is a proven, nature-based approach with the potential to reverse these trends. Research shows that agroforestry can boost crop yields in drylands by 30–58% (World Agroforestry Centre, 2022) and enhance soil organic matter by 36% within just five years (FAO, 2021). Alongside environmental restoration, agroforestry contributes to economic stability and reduces tensions over scarce resources. This brief presents actionable policy recommendations to harness and scale agroforestry's benefits, offering decision-makers a clear and practical roadmap for advancing resilience and food security in East Africa’s drylands.